The Impact of Board Structure on Voluntary Environmental and Energy Disclosure in an Emerging Market - Amalia, Siti; Lesmana, Dadang; Yudaruddin, Yanzil Azizil; Yudaruddin, Rizky (International Journal of Energy Economics and Policy, 2022)
This study aimed to investigate the effect of board structure on voluntary environmental and energy disclosure of listed firms in Indonesia. The study employed a one-step and two-step system generalized method of moments (GMM) using an unbalanced data panel of 356 non-finance companies. The findings showed that board size positively and significantly affected environmental and energy disclosure. Moreover, board independence negatively and significantly influenced environmental and energy disclosure, while women on board and CEO duality have an insignificant impact. The strategic implication showed that adding more members to the board of directors boosted voluntary environmental and energy disclosure.